Therapeutic Interventions for Countering Leishmaniasis and Chagas’s Disease: From Traditional Sources to Nanotechnological Systems - Souto, Eliana B. (Pathogens, 2019)
The incidence of neglected diseases in tropical countries, such as Leishmaniasis and Chagas’s disease, is attributed to a set of biological and ecological factors associated with the socioeconomic context of developing countries and with a significant burden to health care systems. Both Leishmaniasis and Chagas’s disease are caused by different protozoa and develop diverse symptoms, which depend on the specific species infecting man. Currently available drugs to treat these disorders have limited therapeutic outcomes, frequently due to microorganisms’ drug resistance. In recent years, significant efforts have been made towards the development of innovative drug delivery systems aiming to improve bioavailability and pharmacokinetic profiles of classical drug therapy. This paper discusses the key facts of Leishmaniasis and Chagas’s disease, the currently available pharmacological therapies and the new drug delivery systems for conventional drugs.